Genetic detection of Chinese hereditary nonpolyposis colorectal cancer - Cui, Long (World J Gastroenterol, 2004)
AIM: To explore the germline mutations of the two main DNA mismatch repair genes (hMSH2 and hMLH1) between patients with hereditary non-polyposis colorectal cancer (HNPCC) and suspected (atypical) HNPCC. METHODS: Genomic DNA was extracted from the peripheral blood of the index patient of each family, and germline mutations of hMSH2 and hMLH1 genes were detected by PCR-single strand conformation polymorphism (PCR-SSCP) and DNA sequencing techniques. RESULTS: For PCR-SSCP analysis, 67% (4/6) abnormal exons mobility in typical group and 33% (2/6) abnormal exons mobility in atypical group were recognized. In direct DNA sequencing, 50% (3/6) mutation of MMR genes in typical group and 33% (2/6) mutation of MMR genes in atypical group were found, and 4/6 (66.67%) and 1/6 (16.67%) mutations of hMSH2 and hMLH1 were identified in typical HNPCC and atypical HNPCC, respectively. CONCLUSION: Mutation detection of the patients is of benefit to the analysis of HNPCC and, PCR-SSCP is an effective strategy to detect the mutations of HNPCC equivalent to direct DNA sequence. It seems that there exist more complicated genetic alterations in Chinese HNPCC patients than in Western countries.